PERSONAL COMPETENCIES OF CHEMICAL ENGINEERING STUDENT GRADUATES BEFORE ENTERING THE WORLD OF WORK - Rumira, Mayda Su’ad Su'ad; Putri, Leggy Doriyanti Julia; Alfisyahri, Syabrina; Rahmawati, Fira; Alya, Neng Via Nurjanahntul; Patimah, Sri; Sari, Dessy Agustina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
To be able to survive in a world of work that changes and develops dynamically, humans are required to continue to improve their abilities periodically. Companies not only require good academic skills but also additional skills that support the company's needs. Relevant abilities (hard skills) balanced with qualified interpersonal skills (soft skills) will be very helpful in work. This ability is useful for creating career opportunities or improving career paths. So, students are required to have quality personal abilities before entering the workforce. The purpose of scientific writing is to provide a description of the self-competencies needed by a chemical engineering graduate as evaluation material for preparation for entering the real world of work. soft skills needed by a chemical engineering graduate, such as analytical skills, problem-solving skills, good communication skills, teamwork, and leadership skills. In this era of globalization, communication skills intersect with foreign language skills such as English and Japanese. Some multinational companies expect their employees to be able to speak foreign languages for the smooth operation of the company. Various efforts have been made by Chemical Engineering at Universitas Singaperbangsa Karawang in order to accommodate students and help them develop their potential. Through several activities such as chemical engineering software training, procurement of foreign language classes, and routinely holding public lectures by presenting practitioner teachers from companies. It is hoped that chemical engineering graduates from Universitas Singaperbangsa Karawang will have sufficient provisions to face the world of work.